2019
DOI: 10.1108/ijbm-04-2018-0086
|View full text |Cite
|
Sign up to set email alerts
|

Can gamification improve financial behavior? The moderating role of app expertise

Abstract: Purpose The purpose of this paper is to explore potential benefits of gamification (application of game-playing elements) for financial well-being and motivation to save. Design/methodology/approach A preliminary survey of college students explored how gamification principles incorporated into money-savings/personal finance smartphone apps could improve financial well-being. The main study utilized Mechanical Turk participants, exposing them to financial game app descriptions that emphasized social features … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
0
11

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(85 citation statements)
references
References 62 publications
3
52
0
11
Order By: Relevance
“…These findings were strengthened by the average value of experiment class study results as showed in Table 3. The results of this study were supported by [8]. It shows that having experience with a money-savings/financial mobile Advances in Social Science, Education and Humanities Research, volume 377 app impacts individuals subjective financial knowledge.…”
Section: Results and Analysissupporting
confidence: 71%
“…These findings were strengthened by the average value of experiment class study results as showed in Table 3. The results of this study were supported by [8]. It shows that having experience with a money-savings/financial mobile Advances in Social Science, Education and Humanities Research, volume 377 app impacts individuals subjective financial knowledge.…”
Section: Results and Analysissupporting
confidence: 71%
“…fintech, such as improvements in financial management through the facilitation of customer engagement in e-banking usage (e.g. Bayuk and Altobello, 2019;.…”
Section: Contextualization Of Gamificationmentioning
confidence: 99%
“…Regarding points, a study by Xi and Hamari (2019) infers that points can influence competence outcomes. Badges incorporated into gamified applications have also been shown to influence outcomes, including motivation (Bayuk & Altobello, 2019; Huang & Hew, 2018). For instance, a study by Bayuk and Altobello (2019) of a gamified financial app included badges that enhanced knowledge regarding monetary saving.…”
Section: Conceptual Model and Hypothesis Developmentmentioning
confidence: 99%
“…Badges incorporated into gamified applications have also been shown to influence outcomes, including motivation (Bayuk & Altobello, 2019; Huang & Hew, 2018). For instance, a study by Bayuk and Altobello (2019) of a gamified financial app included badges that enhanced knowledge regarding monetary saving. At present, less empirical support currently exists for trophies.…”
Section: Conceptual Model and Hypothesis Developmentmentioning
confidence: 99%